Evaluation of hydrogenated cyanamide in in budbreak, yield and nut quality of pecan - Zuñiga Valenzuela, Rafael; Zuñiga Valenzuela, Elizabeth; Nava Camberos, Urbano; García Hernández, José Luis; Preciado Rangel, Pablo; Puente Valenzuela, Cristo Omar (Ecosistemas y Recursos Agropecuarios, 2024)
Effective chilling hours (EFH) are an environmental factor that influences the development of the walnut tree, by being able to delay sprouting in addition to reducing production. The objective was to evaluate hydrogenated cyanamide (H2CN2), as a HFE compensator in the pecan walnut crop (Carya illinoinensis (Wangenh.) K. Koch). Carrying out dosages of ≈0, ≈ 2.5, ≈ 5 and ≈ 7.5% of cyanamide, evaluating sprouting on different dates. Significant differences were observed in the sprouting evaluations on March 22 and 26. In untreated trees (0%) there was 3.6% sprouting, while in those treated with cyanamide it increased, registering 12.8, 16.4 and 29.4%, respectively. For the date of March 26, the control showed 9.9% sprouting, and the treated ones, 23.5, 28.6 and 54.6%, in the shoot length on the dates of May 3 and June 7, in the control trees. the average shoot length was 4.0 to 4.7 cm; and in treated trees, the average shoot length was 5.7 to 6.2 cm, 6.5 to 7.2 cm and 5.2 to 6.0 cm. In the production variable, the 7.5% treatment showed a statistical difference over the other treatments with an average of 40 kg per tree, the 0, 2.5 and 5% treatments produced 30.1, 33.2 and 34.8 respectively. According to the results obtained, cyanamide influences the development of sprouting and increases production, without reducing the quality of the nut.
Keywords: Cold hours compensator; effective cold hours; pecan production